Ethiopian Biodiversity Institute investment of USD 70,000 in in-situ conservation (based on utilization) following community-based breeding program guidelines - CGIAR Research Program on Livestock (2020)
Ethiopian Biodiversity Institute has a mandate to conserve national animal genetic resources. They have invested in implementation of community-based breeding programs (CBBPs) for low input systems using the ICARDA guidelines.